(untitled) (Islamic Sciences Journal, 2023)
The present study aimed at investigating the effect of using the cognitive modeling strategy in developing the rational thinking in the second grade students in Islamic education. The experimental design (partial control) was selected for two equal groups (experimental and control). Day schools, within the district of Baiji / villages AL- Boutama and Al-hijaj deliberately as a field of experiment. The research sample consisted of (60) students, randomly distributed, and consisted of (30) students for each group and for the safety of the research rewarded the researcher among the research groups in some variables that may be influence in the independent variable (such as chronological age of the students, test, and grades the first course of the Islamic Education). The scientific material of the research was determined by the subjects (7, 8, 9, 10 and 11) of the book of Islamic education scheduled for the second intermediate grade 2018-2019, and (25) behavioral objectives were identified, and the researcher prepared the teaching plans for the two groups.